∫ 0 ∞ ∫ 0 ∞ ∫ 0 ∞ ( 1 + x + y + z ) 7 / 2 d x d y d z
If the multiple integral above can be expressed as b a , where a and b are coprime positive integers, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us change the variables from ( x , y , z ) to ( x , y , z ′ ) where z ′ = x + y + z . Then, d x d y d z = d x d y d z ′ and for particular ( x , y ) , z ′ varies from ( x + y ) to ∞ . Then, ∫ 0 ∞ ∫ 0 ∞ ∫ 0 ∞ ( 1 + x + y + z ) 7 / 2 d x d y d z = ∫ 0 ∞ d x ∫ 0 ∞ d y ∫ ( x + y ) ∞ ( 1 + z ′ ) 7 / 2 d z ′ = 5 2 ∫ 0 ∞ d x ∫ 0 ∞ ( 1 + x + y ) 5 / 2 d y = 5 2 ∫ 0 ∞ d x ∫ x ∞ ( 1 + y ′ ) 5 / 2 d y ′ [ y ′ = x + y ] [ By changing variables from ( x , y ) to ( x , y ′ ) ] = 5 2 ⋅ 3 2 ∫ 0 ∞ ( 1 + x ) 3 / 2 d x = 5 2 ⋅ 3 2 ⋅ 1 2 = 1 5 8
So, a + b = 8 + 1 5 = 2 3
Let a = 1 + x + y + z . The integral becomes ∫ 1 ∞ d a a − 7 / 2 ∬ 0 ≤ x , y x + y ≤ a − 1 d x d y . The integration over x and y is equivalent to finding the area of the region defined by x , y ≥ 0 and x + y ≤ a − 1 , which is a right triangle with legs a − 1 , and therefore area 2 1 ( a − 1 ) 2 . Thus we continue ∫ 1 ∞ 2 1 ( a − 1 ) 2 a − 7 / 2 d a = ∫ 1 ∞ ( 2 1 a − 3 / 2 − a − 5 / 2 + 2 1 a − 7 / 2 ) d a = 2 1 ⋅ − 1 / 2 1 a − 1 / 2 − − 3 / 2 1 a − 3 / 2 + 2 1 ⋅ − 5 / 2 1 a − 5 / 2 ∣ ∣ ∣ ∣ 1 ∞ 2 1 ⋅ 2 − 3 2 + 2 1 ⋅ 5 2 = 1 − 3 2 + 5 1 = 1 5 8 . Thus the answer is 8 + 1 5 = b o x e d 2 3 .
Problem Loading...
Note Loading...
Set Loading...
For Generalizing things a bit let us consider the integral,
F n ( m ) = ∫ 0 ∞ ∫ 0 ∞ ⋯ ∫ 0 ∞ ( 1 + x 1 + x 2 + ⋯ + x n ) m d x 1 d x 2 ⋯ d x n
Noting that, ( 1 + x 1 + x 2 + ⋯ + x n ) m 1 = Γ ( m ) 1 ( ∫ 0 ∞ e − u ( 1 + ∑ i x i ) u m − 1 d u ) and substituting this back into F n ( m ) we have,
F n ( m ) = ∫ 0 ∞ ∫ 0 ∞ ⋯ ∫ 0 ∞ Γ ( m ) 1 ( ∫ 0 ∞ e − u ( 1 + ∑ i x i ) u m − 1 d u ) d x 1 d x 2 ⋯ d x n = Γ ( m ) 1 ∫ 0 ∞ e − u ( ∫ 0 ∞ e − u x 1 d x 1 ) ⋯ ( ∫ 0 ∞ e − u x n d x n ) u m − 1 d u = Γ ( m ) 1 ∫ 0 ∞ e − u ( ∫ 0 ∞ e − u x d x ) n u m − 1 d u = Γ ( m ) 1 ∫ 0 ∞ e − u × u n 1 u m − 1 d u = Γ ( m ) 1 ∫ 0 ∞ e − u u m − n − 1 d u = Γ ( m ) Γ ( m − n )
Put n = 3 , m = 7 / 2 to derive the answer as 1 5 8